Análise das diretrizes e estratégias construtivas para a cidade de Pau dos Ferros/RN - Vidal Júnior, José (Universidade Federal Rural do Semi-Árido, 2018)
Achieving satisfactory environmental performance encompasses adequate architectural planning by engineers, architects, designers and other professionals in the construction industry, given the different climatic conditions. It is known that the main role of the building is to guarantee its users comfort and comfort, and the guidelines of thermal comfort are directly associated with the satisfaction of its user, giving it a thermally comfortable environment. The present work is the result of a technological and bibliographical analysis done in two single-family homes, arranged in different neighborhoods, but with the same constructive characteristics in the city of Pau dos Ferros-RN. The analysis is based on the NBR 15220 that deals with thermal performance for dwellings in its Bioclimatic Zoning. For the study, the Zone in question was 7 and, based on its provisions, the study was operated. After data collected locally and confronted with the guidelines of the standard, it was noticed that both properties were outside the parameters for their zoning, and, on the basis of this, constructive solutions are proposed to repair them.
Keywords: Conforto térmico; Desempenho; Construção civil; Thermal comfort; Performance; Construction; ENGENHARIAS::ENGENHARIA CIVIL